Analisis Faktor Yang Mempengaruhi Tingkat Kecemasan Pasien Pre Operasi Di Rumah Sakit Umum Daerah Kabupaten Dompu Tahun 2023 - Mukhlis, Mukhlis; Ayatullah, Ayatullah; Kadafi, Amirul (Barongko: Jurnal Ilmu Kesehatan, 2024)
Anxiety is an emotional reaction that arises from uncertain and non-specific causes that can cause feelings of discomfort and feel threatened. Anxiety causes physical and emotional disturbances, increasing body temperature through hormonal and innervation stimuli. Various causes of anxiety in preoperative patients include situations such as personal, environmental, maturational, educational level, stimulus characteristics, and individual characteristics. The purpose of this study was to determine the factors that affect anxiety in preoperative patients at Dompu Regency Hospital. The research design used non-experimental with analytic survey type and cross-sectional approach. respondents experienced severe anxiety level as many as 4 (6.70%) respondents, moderate anxiety as many as 15 (24.40%) respondents, mild anxiety 28 (46.70%) respondents. The relationship between factors of age, gender, education, marital status, type of surgery, surgical experience is enough to influence respondents in deciding attitudes towards preoperative anxiety. Family support and attention calmed the respondents so that anxiety decreased.